2018
DOI: 10.24263/2304-974x-2018-7-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and application of flowers of false acacia (Robinia pseudoacacia L.)

Abstract: Introduction. The study was carried out to determine the chemical composition and biological activity of false acacia flowers and their products (concrete and syrups) grown in Bulgaria. Materials and methods. Concrete was obtained by extraction with n-hexane and its chemical composition was determined by GC-MS. Syrups with different concentrations have been obtained and their polyphenols content, antimicrobial and antioxidant activity were established. Result and discussion. The yield of concrete was 1.06% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Thus, in the case of RP, Marinas et al (2014) [29] found a content of 26.67 mg GAE/g, and for MA, the level was reported at 14.8 mg GAE/g [30]. Higher values of phenolic compounds in the flowers (0.77 mg GAE/mL) were observed compared to syrup 60 • Brix (0.06 mg GAE/mL) and R. pseudoacacia syrup 70 • Brix (0.14 mg GAE/mL) [31]. Serbian RP showed values of 74.28 ± 1.73 for TPC (mg GAE/g) [29], while Arnold et al (2015) [32] reported a phenolic content of 20.55 ± 2.56 mg GAE/g in the OS extract.…”
Section: Chemical Composition Of Extractsmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, in the case of RP, Marinas et al (2014) [29] found a content of 26.67 mg GAE/g, and for MA, the level was reported at 14.8 mg GAE/g [30]. Higher values of phenolic compounds in the flowers (0.77 mg GAE/mL) were observed compared to syrup 60 • Brix (0.06 mg GAE/mL) and R. pseudoacacia syrup 70 • Brix (0.14 mg GAE/mL) [31]. Serbian RP showed values of 74.28 ± 1.73 for TPC (mg GAE/g) [29], while Arnold et al (2015) [32] reported a phenolic content of 20.55 ± 2.56 mg GAE/g in the OS extract.…”
Section: Chemical Composition Of Extractsmentioning
confidence: 85%
“…All extracts had a colony-stimulating action (RP ↑ > CV ↑ > MO ↑ > OS ↑), being one of the few microorganisms more difficult to control [52]. In the cited literature [53], MO proved a weak effect on S. aureus, RP showed no effect on S. cholerae in any of the four types of extracts tested, and OS proved no effect against S. aureus (PeruMycA 7) in concentrations higher than 250 µg/mL [1, 29,31].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The thorns, a highly unwanted feature from the village dwellers' point of view, play a role in protecting the plant from herbivores (including human beings as shown above). The bioactive compounds present in all parts of the plant (except the flowers), and especially in the bark, may be toxic to human and non-human animals (Stankov et al 2018;Tyśkiewicz et al 2019). Thus, they play a similar role to thorns.…”
Section: Case Studiesmentioning
confidence: 99%
“…The antioxidant activity of the vegetal extracts may represent valuable information, as it may partly explain their antitumoural effect. Currently, there are numberless data in the literature regarding the antioxidant activity of vegetal compounds, which are generally correlated to their anti-aging and antitumoural action [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%